Comparative study of energy efficiency and environmental impact in magnetic field assisted and conventional electrical discharge machining. (20th March 2019) - Ming, Wuyi; Zhang, Zhen; Wang, Shengyong; Zhang, Yanming; Shen, Fan; Zhang, Guojun
Abstract: Electrical discharge machining is a significant non-traditional technique, widely used in the precise manufacturing field. However, the electrical discharge machining process possesses plenty of energy consumption and hazardous exhaust emissions. Since a sustainable machining technique, external magnetic field assisted, could dramatically develop sustainable machining performance of electrical discharge machining process, this paper presents a comparative study energy efficiency and environmental impact in magnetic field assisted electrical discharge machining and conventional electrical discharge machining. A novel thermo-physical model was proposed to calculate energy distribution under the single/continuous discharge, which was verified by a series of corresponding experiments. Then, based on simulation and experimental methods, a comparative study on the magnetic field assisted electrical discharge machining and conventional electrical discharge machining was conducted to analyze the discharge energy flowing and temperature distribution of workpiece, electrode tool and debris. Moreover, the effects of external magnetic field on the machining performance, environmental impacts and energy efficiency were presented. Eventually, it can be found out that the effect of magnetic field contributes to increasing energy utilization efficiency by 15.2%, material erosion efficiency by 22.6%, and material removal rate by 21.9%. To balance energy efficiency and surface roughness (Ra), the optimal parameter combination is obtained as below: magnetic field intensity: 0.2T, discharge current: 7–9A, and pulse duration: 300s. Highlights: Magnetic field assisted EDM improve energy efficiency and environmental impact. A thermo-physical model is proposed to calculate energy distribution of MF-EDM process. Sustainable machining performance of EDM and MF-EDM are comparatively investigated. The optimal parameter is: magnetic field intensity: 0.2T, current: 7∼9A, and pulse duration: 300μs.